(untitled) (PERcursos Linguísticos, 2022)
This article has as its theme the training of translators and interpreters of Libras/Portuguese. The questions that guided the study were: What is the view of former students and graduates about their training in the course offered by UFG? What are the perceptions of these students that could add better practices in the course? And to answer them, the objective was set to identify the vision of graduates and completers about the training offered by the course of Letters: Translation and Interpretation in Libras/Portuguese and discuss the perception of graduates and completers about the course of Letters: Translation and Interpretation in Libras/Portuguese at UFG. The study was a qualitative research (ESTEBAN, 2010, p. 127) and data were collected using a questionnaire with open and objective questions. After collecting and analyzing the data, it was concluded that the training offered has positive elements and elements to be improved, such as the possibility of practical experiences during training.